Mosque Waqf Land Utilization for Madrasahs and Posyandu Through Islamic and Indonesian Legal Perspectives - Muhammad Yusuf Siddik; Asep Riyadi; Kiki Kiki; Mukhsin Mukhsin; Ilzam Hubby Dzikrillah Alfani (Alhurriyah, 2026)
This study aims to examine the legality of utilizing mosque waqf land for madrasahs and Posyandu from the perspectives of Islamic law and Indonesian positive law and to formulate an integrative legal framework that balances the sanctity of mosque waqf with contemporary public interests. The issue arises from increasing community demands for educational and primary healthcare facilities while maintaining the original religious function of mosque waqf. This research employs qualitative normative legal research using a library research method. The study applies statutory, conceptual, and comparative approaches by examining Law No. 41 of 2004 on Waqf, the principles of maqāṣid al-sharīʿah, classical fiqh of the four Sunni schools, contemporary Islamic legal scholarship, and relevant Indonesian regulations. Data were collected through documentary studies and analyzed using descriptive, comparative, and synthetic methods. The findings demonstrate that utilizing mosque waqf land for madrasahs and Posyandu is legally permissible provided that the mosque's principal religious function is preserved, the utilization promotes public benefit, complies with national legal requirements, and is approved through collective deliberation. The study develops a four-pillar integrative model consisting of al-taqdīs, al-maṣlaḥah, al-mashrūʿiyyah, and al-shūrā as normative guidelines for mosque waqf governance, thereby contributing to the harmonization of classical Islamic jurisprudence, contemporary legal thought, and Indonesian positive law in strengthening sustainable community welfare.